The Mellow Babies parenting programme: role of group processes and interpersonal change mechanisms - Jessica Tanner; Philip Wilson; Philip Wilson; Daniel Wight; Lucy Thompson (Frontiers Media S.A., 2024)
IntroductionGroup-based parenting programmes have specific mechanisms of change compared to individual delivery. The Mechanisms of Action in Group-based Interventions framework (MAGI); distinguishes between interpersonal and intrapersonal mechanisms of change. This paper articulates a theory of change for Mellow Babies, a 14-week attachment-based group parenting programme for mothers of infants aged under 18 months, identifying the inter and intrapersonal change processes.MethodsThirty-two semi-structured interviews were conducted with mothers and practitioners who participated in Mellow Babies, including twenty post-group interviews and nine telephone fidelity checks. Data were analysed using Deductive Qualitative Analysis based on the components identified within the MAGI framework.ResultsKey interpersonal change mechanisms included: 1. Normalisation through social comparisons; 2. Validation and cognitive reframing through group feedback; 3. Peer support, offering accountability for the implementation of new habits, and providing opportunities to give and receive advice; and 4. Social and experiential learning, including internalisation of group responses leading to increased self-compassion. Intrapersonal change mechanisms were: 1. Developing new self-insight, including parenting self-awareness; 2. Increasing parenting knowledge and understanding of infant development; 3. Having time and space for self; 4. Motivation to implement new habits. Interpersonal change mechanisms had a moderating role on intrapersonal change mechanisms and subsequent programme outcomes.DiscussionThe contribution of group processes and interpersonal mechanisms of change are often overlooked within programme evaluations. Findings from this study implicate their mediating role on intrapersonal change mechanisms and subsequent programme outcomes. It is important for programme deliverers and evaluators to understand the interrelationships between group processes, change mechanisms and programme outcomes to optimise efficacy and ensure cross-contextual replicability.